Atlantic Forest meets the Cerrado: floristic, structure and species distribution of an ecotonal tree community - Sabino, Gabriel Pavan [UNESP]; Kamimura, Vitor de Andrade [UNESP]; Marcusso, Gabriel Mendes [UNESP]; Monteiro, Reinaldo [UNESP] (Univ Federal Mato Grosso, 2021)
We evaluated the floristic and structural composition of a tree community in an ecotone between Cerrado (cerradao) and Atlantic Forest (seasonal semideciduous forest) domains located in Porto Ferreira State Park (PFSP), southeastern Brazil. We compared the floristic relationships of this ecotone with those of previous surveys carried out on the same vegetation types and checked the species distribution among the Brazilian biomes. We sampled all living trees with PBH>10 cm in 64 10x10 m plots (0.64 ha), totaling 1,755 individuals belonging to 101 species and 37 families. The richest families were Myrtaceae (13 spp.) and Fabaceae (11 spp.), and Siparuna guianensis was the most abundant species (188 individuals). We reported two threatened species. A great number of species are widely distributed, occurring in different Brazilian biomes. Floristic similarity values were low among the selected studies, but our sampled community clustered with communities of cerradao and ecotone areas of previous surveys. Our results corroborate that ecotonal areas have great tree diversity and the predominance of widely distributed species. This fact, combined with the vegetation thickening verified through historical photographs, reinforces that the study area belongs to an under-changing ecotone.
Keywords: ecotone; cerradao; seasonal semideciduous forest; phytogeography; floristic similarities